2015
DOI: 10.1016/j.dmpk.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine regulates the expression of UDP-glucuronosyltransferase (UGT) in humanized UGT1 mouse brain

Abstract: UDP-glucuronosyltransferase (UGT) is a family of enzymes that catalyze the glucuronidation of various compounds, and thereby has an important role in metabolism and detoxification of a large number of xenobiotic and endogenous compounds. UGTs are present highly in the liver and small intestine, while several investigations on quantification of UGT mRNA reported that UGTs were also expressed in the brain. However, reported expression patterns of UGT isoforms in human brain were often incongruous with each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In the hUGT1 mice, UGT1A1, 1A3, 1A6, and 1A10 were expressed in the brain (Fig. 1B), which was in agreement with our previous study (Sakamoto et al, 2015). The expression pattern of UGT1As in the brain was very similar between human and hUGT1 mice (Fig.…”
Section: Resultssupporting
confidence: 81%
“…In the hUGT1 mice, UGT1A1, 1A3, 1A6, and 1A10 were expressed in the brain (Fig. 1B), which was in agreement with our previous study (Sakamoto et al, 2015). The expression pattern of UGT1As in the brain was very similar between human and hUGT1 mice (Fig.…”
Section: Resultssupporting
confidence: 81%
“…Herein, genistein-7-glucoside has a higher affinity for β-glucosidase than quercetin-4′-glucoside thus the former shows a higher deglycosylation rate, whereas some other glycosides such as quercetin-3,4′-diglucoside, quercetin-3-glucoside, kaempferol-3-glucoside, quercetin-3-rhamnoglucoside, and naringenin-7-rhamnoglucoside prefer to remain unchanged (Day et al, 1998). This intracellular reaction is regarded as a vital way to expose hydroxyl group of xenobiotics for further conjugation Cheng et al (1999), Margaillan et al (2015), Wong et al (2009), Finel et al (2005), King et al (1999), Mostaghel et al (2016), King et al (2000), Teubner et al (2007), Cheng et al (1998), Cheng et al (1999), Barbier et al (2000), Knights et al (2013), Chimalakonda et al (2011), Riches et al (2009), Ghosh et al (2013), Sakamoto et al (2015), Lu et al (2015), Guidry et al (2017), Kurogi et al (2017),…”
Section: Phase II Metabolism In Enterocytesmentioning
confidence: 99%
“…Subsequently, it was demonstrated that treatments of hUGT1 mice with TCDD, PCN, phenytoin, and fatty acids caused induction of human UGT1A1 in the liver, indicating that the promoter region of human UGT1A1 in hUGT1 mice is responsive to AhR, PXR, and PPAR activations as well [11,34,52]. It was also shown that human UGT1A isoforms expressed in extrahepatic tissues such as small intestine, skin, and brain were inducible by xenobiotics in hUGT1 mice [5355]. hUGT1 mice were also useful to understand the transcriptional regulation of human UGT1A isoforms in the liver during pregnancy [56].…”
Section: Humanized Ugt1 (Hugt1) Mice and Expression Of Human Ugt1smentioning
confidence: 99%